NUMERICAL INVESTIGATION OF HEAT TRANSFER ENHANCEMENT IN A CIRCULAR TUBE USING RIBS OF SEPARATED PORTS ASSEMBLY - Rashid, Farhan Lafta; Altaie, Arkan; Hasan, Moayed R. (European Scientific Journal, ESJ, 2014)
The paper deals with numerical investigation for the influence of separated ports assembly ribs on heat transfer ina steel tube of 50 cm long , outside diameter of 60 mm and inside diameter of 30 mm with constant outside surface temperature of 1000, 1200 and 1400 Ko.The renormalization group k-ε model is used to simulate turbulence in ANSYS - FLUENT 14.5. The ribs assembly (5x5 mm triangle passage) were fitted in the tube and separated by 8cm pitch. Results of temperature and velocity distribution along the tube center line for the case of tube with internal ribs were compared with that of plain tube , these results show that the use of internal ribs enhance the heat transfer rate and found to possess the highest performance factors for turbulent flow.